(untitled) (Journal of Plant Disease Sciences, 2021)
Xanthomonas citri subsp. citri causes citrus canker, which is one of the most serious diseases. The bacterium infects the twigs, petioles, fruit stalks, and fruits, causing acid lime loss in both quality and quantity. On the nutrient agar medium, Xanthomonas citri subsp. citri (Xcc) was successfully isolated, from different agroclimatic zones of Maharashtra. All of the Xcc isolates’ pathogenic potential was confirmed, and it was found that isolates Xcc-6, Xcc-7, Xcc-10, Xcc-11, and Xcc-12 were highly pathogenic to commence minute canker lesions and fully developed symptoms after 17-22 days. Molecular detection by polymerase chain reaction with speciûc primers J-pth 1/Jpth-2, J Rxg/Rxc2,Xac-01/Xac-02, M+/M- and Ms+/Ms- was performed on fourteen isolates. The patterns showed by PCR analysis were identical for all the isolates tested confirming their identity as Xanthomonas citri subsp. citri. The highly virulent isolates were sent to the Agri-genome Pvt. Ltd., Hyderabad for sequencing. The result of DNA sequencing were searched against other sequences deposited in the NCBI gene bank database using NCBI-BLAST and all five isolates showed 100 per cent similarity with Xanthomonas citri subsp. citri genome.